ПЕРЕБУДОВИ 11q23/MLL ПРИ ГОСТРИХ ЛЕЙКЕМІЯХ У ДОРОСЛИХ - Zotova, O.V.; Lukianova, A.S.; Valchuk, M.O.; Karol, Yu.S.; Shalay, O.O.; Novak, V.L.; Loginsky, V.E. (PH Akademperiodyka, 2023)
Summary. Aim: To detect the frequency, diagnostic and prognostic significance of 11q23/MLL rearrangements and to determine the chromosomes that are most frequently involved in 11q23/MLL abnormalities in adult acute leukemia (AL). Materials and Methods: Cytogenetic investigations of bone marrow and/or peripheral blood cells from 140 patients with acute myeloid leukemia (AML) and 57 patients with acute lymphoblastic leukemia (ALL) were performed. The methods of conventional cytogenetics (GTG-banding) and fluorescence in situ hybridization were used. Results: Chromosomal abnormalities in leukemia cells were found by conventional cytogenetic methods in 80 (57%) and 37 (65%) adult patients with AML and ALL, respectively. 11q23/MLL rearrangements were found in 7 (5%) and 8 (14%) patients with AML and ALL, respectively. Among them, 8 (53.4%) patients had translocations, 2 (13.3%) — had deletions and 5 (33.3%) patients had trisomies or tetrasomies of chromosome 11. With respect to the distribution of partner chromosomes involved in 11q23/MLL translocations chromosome 4 was found to participate in 3 (37.5%) cases of 11q23/MLL translocations, 9 — in 2 (25%) cases and chromosomes 10, 14 and non-identified chromosome were involved in 1 (12.5%) case each. Nine patients (60%), besides abnormal ones, had 9–86% normal metaphases in their karyotypes. Of 15 patients with 11q23/MLL rearrangements, 5 (33%) patients had only 11q23/MLL rearrangements, whereas other 10 (67%) — had additional cytogenetic abnormalities, besides 11q23/MLL rearrangements. Conclusions: Chromosomal abnormalities of various kinds were found in 57% and 65% adult patients with AML and ALL, respectively. The frequency of 11q23/MLL rearrangements in patients with AML and ALL was 5% and 14%, respectively. Since AL patients with 11q23/MLL rearrangements are attributed to cytogenetic categories of AL with a poor or intermediate risk prognosis, cytogenetic methods should be included in the standard examination of AL patients for diagnosis, prognosis and selection of the optimal treatment strategy.